Pembinaan Adab-Adab Bersuci (Fiqih Thoharoh) Pada Anak-Anak di Komplek Perumahan The Green Indralaya Kelurahan Timbangan Kecamatan Iindralaya Utara Kabupaten Ogan Ilir Sumsel - Endang Switri; Abdul Gofur; Apriyanti Apriyanti; Sri Safrina (JPM: Jurnal Pengabdian Masyarakat, 2020)
This guidance and counseling aims to develop knowledge to the community by helping children and the community in science in worship, that before carrying out a worship one must first purify, whether you want to pray, fast, do Umrah, Hajj and other acts of worship. Then the implementation of community service / guidance and counseling uses the method of implementation by means of extension and demonstration; Counseling using conventional methods, namely lectures to convey material about the manners of purification (fiqih thoharoh), while the demonstration / practice method uses demonstration methods and experimental methods, namely practicing the method of ablution ', istinjak and bathing. Then after that, hold a question and answer using the question and answer method, then give rewards to children who have asked and all children are also given rewards to them by asking them questions. As for the results of the implementation of community service that has been carried out, the children were enthusiastic about participating in the material and demonstrating how to purify. And they (the children) hope that we often come to them or carry out our next service with the theme of how to purify the pronunciation of the hijaiyah letters so that in reading the Al-Qur'an and short prayers, the reading hadiths lead to good and correct reading